ANALISIS PENGARUH KERUSAKAN JALAN TERHADAP KECEPATAN PERJALANAN - Cut liliiza Yusra; Muhammad Isya; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2018)
Road damage that occurs in some road segments that cause huge losses, especially for road users. It is worth noting that there is no decrease in road quality due to road surface damage. The purpose of this study is to analyze the effect of the rate of damage with the speed of travel. This research took place on Lueng Mane - Tadu Raya Road segment, Kuala Tadu Sub-District, Nagan Raya District over 2000 meters divided into 20 segments with a segment length of 100 meters. Primary data were collected by actual field survey that is road geometric data, extensive damage to roads and travel speed. The results show that road damage is very influential to the speed of travel, as seen in segment 11 with the value of 18 very ugly road conditions with travel speed reached 28,324 km/h, while in segment 6 PCI value of 100 perfect road conditions (Excellent) travel speed reaches 59,90 km/h, so the equation Y = 0,3202x + 21,264. This shows that the higher the level of damage the lower the speed of travel, the lower the level of damage the higher the speed of travel.